IL-6: The Link Between Inflammation, Immunity and Breast Cancer - Chen, Juan; Wei, Yanghui; Yang, Weiqin; Huang, Qingnan; Chen, Yong; Zeng, Kai; Chen, Jiawei (Frontiers in Oncology, 2022)
Breast cancer is one of the leading causes of mortality in females. Over the past decades, intensive efforts have been made to uncover the pathogenesis of breast cancer. Interleukin-6 (IL-6) is a pleiotropic factor which has a vital role in host defense immunity and acute stress. Moreover, a number of studies have identified the physiological and pathological roles of IL-6 in inflammation, immunity and cancer. Recently, several IL-6 signaling pathway-targeted monoclonal antibodies have been developed for cancer and immune therapy. Combination of IL-6 inhibitory antibody with other pathways blockage drugs have demonstrated promising outcome in both preclinical and clinical trials. This review focuses on emerging studies on the strong linkages of IL-6/IL-6R mediated regulation of inflammation and immunity in cancer, especially in breast cancer.